Post-traumatic Carotid Artery Dissection and Infarction - Yılmaz Seçilmiş; Yunus E Doğan (Galenos Yayinevi, 2023)
Post-traumatic internal carotid artery dissection is a very rare condition in children that occurs after blunt force trauma to the head or neck. A 15-year-old male patient who presented to the emergency room with weakness after a trauma to his neck sustained during a physical altercation is presented.